This is Pollock - Ingram, Catherine; Arkle, Peter (London: Laurence King Publishing, 2014)
"In 1956, Time magazine referred to Pollock as 'Jack the Dripper'. His iconic paintings stretch out with the generosity and scale of America's Western landscape where the artist grew up. Pollock said that he painted 'out of his conscious': the cathartic dribbled paint reflected his troubled mind. This book traces Pollock's career and discusses how his loose, individual style was used as a political weapon in the Cold War, representing America as the free, democratic nation. Illustrations simplify the theory and reveal the hidden meaning behind the mesh of painted lines."--Amazon.com.
Includes bibliographical references (page 80).
Keywords: Pollock, Jackson, -- 1912-1956.; Artet boterore; Arti vizual-piktura; Arti modern; Painters -- United States-Shtetet e Bashkuara -- Biography-biografia -- Artiste amerikane; Painting, American -- 20th century-shekulli i 20-te; Arti bashkekohor -- Amerike; Piktore amerikane-Pollok-biografia-historia-ilustrime-ilustratore-fotografia-animacioni